(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
This paper manages the Indian Freedom Struggle and the contribution of Indian women in this war of Independence. The article discloses to us the participation of women of Punjab in the nationalist movement from 1901-10, 1911-20, 1921-30, 1931-40 and 1941-47. In 1901-10, political changes in the area of Bengal influenced Punjabi women and couple of women demonstrated their sensitivity for the Bengali people. The decade 1911-20 was the most vital decade as the Jallianwala Bagh catastrophe and consequently the military law of 1919 went about as an impetus for making women cognizance for battling for the freedom of India. At that point these women unfortunate casualties and option thoughtful women specifically hopped into the Non-Cooperation movement of 1920. The decade 1921-30, saw the immediate involvement of young ladies of Punjab in the freedom struggle and these women came into the contact of M.K.This examination manages the Indian freedom struggle and contribution of Indian women in this war of independence. The history of Indian Freedom Struggle would be inadequate without mentioning the contributions of women. The forfeit made by the women of India will possess the chief place. They battled with genuine soul and fearless mettle and confronted different torments, abuses and hardships to gain us freedom. Women effectively took an interest in the progressive movements for social changes amid the national struggle for Independence. The participation of women was not limited to one kind of action, for example, the non-savage Satyagraha Movement. A large number of Indian women committed their lives for getting freedom of their lives for acquiring freedom of their homeland.